PENGARUH KOMBINASI PUPUK TRICHOKOMPOS DAN PUPUK NPK TERHADAP KANDUNGAN PROTEIN KASAR DAN SERAT KASAR RUMPUT PAKCHONG - Apriliana, Anisa Dwi; Liman, Liman; Erwanto, Erwanto; Muhtarudin, Muhtarudin (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2025)
This study aims to interact and influence the use of a combination of trichocompost and NPK fertilizers on the crude protein and crude fiber content of pakchong grass. This research was conducted from October to December 2023 at the Integrated Field Laboratory Greenhouse, Faculty of Agriculture, University of Lampung, Bandar Lampung. This study used an experimental method with a Factorial Completely Randomized Design (CRD) with 2 factors arranged in a 4 × 4 factorial experiment with 3 replications. The treatments given were a combination of the first factor, namely T0: without trichocompost, T1: 15 tons/ha trichocompost, T2: 30 tons/ha trichocompost, T3: 45 tons/ha trichocompost with the second factor which is K0: no NPK fertilizer, K1, 100 kg/ha urea+50 kg/ha TSP+50 kg/ha KCL, K2: 150 kg/ha urea+75 kg/ha TSP+75 kg/ha KCL, K3: 200 kg/ha urea+100 kg/ha TSP+100 kg/ha KCL. The variables observed were crude protein and crude fiber content. The data obtained were analyzed using analysis of variance and continued with the Least Significant Difference Test (LSD) at the 5% level. The results showed that the use of NPK fertilizer gave a significant effect (P <0.05) on the crude protein content and crude fiber content of pakchong grass. The results of the Least Significant Difference (LSD) test on crude protein showed that K3 treatment was significantly different from K0, K1 and K2 (K3: 15.53%; K2: 13.46%; K1: 13.44%; K0: 12.10%). While the crude fiber content of K3 treatment is significantly different from K1 (K3: 31.49%; K1: 28.16%).